Exploring Teachers' Perceptions of Number Concepts and Arithmetic Operations in Elementary Education - Rini Sulastri; Lia Ardiansari (Didaktik Matematika, 2025)
This study explores elementary school teachers' understanding of the concept of number and arithmetic operations through a phenomenological approach. The purpose of this study is to explore and understand teachers' subjective experiences in interpreting and teaching these concepts, and to emphasize the importance of individual perspectives in shaping their understanding. Teachers' subjective experiences are considered crucial because they influence the way they teach and explain mathematical concepts to students, as well as shaping students' concept images. This study involved 10 elementary school teachers who were selected using purposive sampling techniques to ensure diversity in experience and educational background. Data analysis was conducted using the phenomenological thematic analysis method to identify key themes and patterns in teachers' experiences. The findings of the study revealed significant differences between teachers' understanding and scientific conceptions, referred to as Zone Concept Image Differences (ZCID). The conclusion of this study shows that teaching the concept of number and arithmetic operations is often constructed narrowly, thus not supporting the development of broader thinking in students.